Diverse profiles of N-acyl-homoserine lactones in biofilm forming strains of Cronobacter sakazakii. Issue 3 (3rd April 2017) - Singh, Niharika; Patil, Amrita; Prabhune, Asmita A.; Raghav, Mamta; Goel, Gunjan
ABSTRACT: The present study investigates the role of quorum sensing (QS) molecules expressed by C. sakazakii in biofilm formation and extracellular polysaccharide expression. The QS signaling was detected using Chromobacterium violaceum 026 and Agrobacterium tumefaciens NTL4(pZLR4) based bioassay. Long chain N-acyl-homoserine lactones (AHLs) with C6- C18 chain length were identified using High Performance Liquid Chromatography and Liquid Chromatography-High Resolution Mass Spectrometry. A higher Specific Biofilm Formation (SBF) index ( p < 0.05) with the presence of genes associated with cellulose biosynthesis ( bcsA, bcsC and bcsG ) was observed in the strains. AHLs and their mechanisms can serve as novel targets for developing technologies to eradicate and prevent biofilm formation by C. sakazakii .